KAJIAN EFEKTIVITAS KEGIATAN DAN ANGGARAN UNIT KERJA DI BADAN TENAGA NUKLIR NASIONAL - Sri Agustini (Universitas Pamulang, 2017)
STUDY OF EFFECTIVENESS OF ACTIVITY AND BUDGET OF UNIT WORK IN NATIONAL NUCLEAR ENERGY AGENCY. In implementing national development programs and activities, the National Nuclear Energy Agency (BATAN) as a government agency is increasingly required to adapt to changes in government management systems that demand accountability principles, where every state administration must be accountable for the performance or outcomes of the entire program and its activities to the community for the use of resources and authority given (BATAN 2016). The Human Resources Profile of BATAN is dominated by male gender groups. While the class of employees is dominated by Group III. Based on the educational group, the most educated staff S1 / D4 dominated, followed by an employee who educated D3 / Bachelor of Youth. Based on the functional group, the functional functionaries of the Nuclear Institute dominate, followed by the functional group of researchers. The achievement of BATAN's performance and budget activities in 2016 has not met the target. From the target of 100% achievement, only 95.74% realized. While the target achievement of the budget of 101.68% only obtained realization 95,71%.